2015
DOI: 10.1038/srep18502
|View full text |Cite
|
Sign up to set email alerts
|

A lipasin/Angptl8 monoclonal antibody lowers mouse serum triglycerides involving increased postprandial activity of the cardiac lipoprotein lipase

Abstract: Lipasin/Angptl8 is a feeding-induced hepatokine that regulates triglyceride (TAG) metabolism; its therapeutical potential, mechanism of action, and relation to the lipoprotein lipase (LPL), however, remain elusive. We generated five monoclonal lipasin antibodies, among which one lowered the serum TAG level when injected into mice, and the epitope was determined to be EIQVEE. Lipasin-deficient mice exhibited elevated postprandial activity of LPL in the heart and skeletal muscle, but not in white adipose tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 63 publications
7
81
0
Order By: Relevance
“…2e, whereas Angptl4 is upregulated due to the elevated circulating glucocorticoid levels34. On one hand, reduced amounts of the Angptl8 protein augments LPL activity specifically in heart and skeletal muscles35, and thus promotes the hydrolysis of VLDL-TG to result in the increased circulating NEFA concentrations. On the other hand, increased amounts of Angptl4 protein decreases LPL activity in an adipose-specific manner36, and promotes intracellular lipolysis in adipocytes37.…”
Section: Discussionmentioning
confidence: 99%
“…2e, whereas Angptl4 is upregulated due to the elevated circulating glucocorticoid levels34. On one hand, reduced amounts of the Angptl8 protein augments LPL activity specifically in heart and skeletal muscles35, and thus promotes the hydrolysis of VLDL-TG to result in the increased circulating NEFA concentrations. On the other hand, increased amounts of Angptl4 protein decreases LPL activity in an adipose-specific manner36, and promotes intracellular lipolysis in adipocytes37.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its role in lipid regulation, ANGPTL8 has been also suggested as a potential therapeutic target for dyslipidemia. 21,68 In addition, because the ANGPTL8 level has been shown to be increased in obesity and in people with MetS 46 we evaluated the potential association between ANGPTL8 and low-grade inflammation and found a positive association between ANGPTL8 and hsCRP. 46 A positive association between ANGPTL8 and hsCRP has been also found in women diagnosed with polycystic ovary syndrome.…”
Section: Angtpl8 and Its Interaction With Other Biomarkersmentioning
confidence: 99%
“…Whole-body ANGPTL8 knockout mice (ANGPTL8 -/-, B6; 129S5-Angptl8 tm1Lex /Mmucd) were a gift from Dr. Ren Zhang at Wayne State University (Michigan, USA) and were originally obtained from the Mutant Mouse Resource Research Centers (7). Mice were fed either regular chow or a high-fat diet (HFD; Research Diets, D12492), where indicated.…”
Section: Angptl8 Knockout Micementioning
confidence: 99%